(عمل الاطفال مشكلة لابد من الحد منها (بحث مستل من رسالة ماجستير (Journal of the College of Education for Women, 2019)
This study focuses on the phenomenon of child labour, which is regarded as a problem not only in Iraq or in developing countries but also in many other countries around the world .In fact, this problem is ignored and not given enough attention for there are millions of children working and doing different works in economically poor societies. Those children often work for long hours and are being exploited, doing works incompatible with their abilities and energy, preventing them from enjoying their childhood, developing both mentally and physically and joining school. The research introduced some suggestions aiming at preventing children from all forms of harmful and unhealthy works are presented. In fact, this is the very aim that most governments try to achieve in order to prevent children from doing such works and to provide some serious alternatives as not to return to such works again.